Research on the Strength Characteristics and Crack Propagation Law of Noncoplanar Nonthrough Jointed Rock Mass by PFC2D - Qingzhi Chen; Yuanming Liu; Shilong Mei; Kai Cao; Bin Du; Wei Wang (Advances in Civil Engineering)
In this study, five groups of numerical models with different conditions were established by using PFC2D (particle flow code) to simulate the direct shear tests of noncoplanar nonthrough jointed rock mass. It is proved that normal stress and shear rate, as well as the connectivity rate, relief angle, and inclination angle of joints, have significant influence on the strength characteristics, number of cracks, and the stress of the rock mass according to measurement taken at five different measurement circles in the rock mass. Moreover, it is determined that in the process of shearing, no matter which group of tests are conducted, the number of cracks in the rock mass caused by tension is far more than that caused by the shear action. In other words, the failure of rock mass with different planes and discontinuous joints is mainly caused by the tension in the process of the direct shear test.